2009
DOI: 10.1084/jem.20082460
|View full text |Cite
|
Sign up to set email alerts
|

Omega-1, a glycoprotein secreted by Schistosoma mansoni eggs, drives Th2 responses

Abstract: Soluble egg antigens of the parasitic helminth Schistosoma mansoni (S. mansoni egg antigen [SEA]) induce strong Th2 responses both in vitro and in vivo. However, the specific molecules that prime the development of Th2 responses have not been identified. We report that omega-1, a glycoprotein which is secreted from S. mansoni eggs and present in SEA, is capable of conditioning human monocyte-derived dendritic cells in vitro to drive T helper 2 (Th2) polarization with similar characteristics as whole SEA. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
330
1
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 327 publications
(352 citation statements)
references
References 34 publications
19
330
1
2
Order By: Relevance
“…SEA is a complex mixture of proteins, glycoproteins, and glycolipids (28,29), and our studies show that SEA-mediated IL-1β production was abolished upon heat inactivation and proteinase K digestion, demonstrating that the responsible component might be a protein. Interestingly, the inactivation of SEA did not alter the TNF-α suppression, suggesting that different components within SEA can act in tandem and thus balance ongoing immune responses.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…SEA is a complex mixture of proteins, glycoproteins, and glycolipids (28,29), and our studies show that SEA-mediated IL-1β production was abolished upon heat inactivation and proteinase K digestion, demonstrating that the responsible component might be a protein. Interestingly, the inactivation of SEA did not alter the TNF-α suppression, suggesting that different components within SEA can act in tandem and thus balance ongoing immune responses.…”
Section: Discussionmentioning
confidence: 94%
“…This finding presents the possibility that the potential Syk-coupled receptor, which is activated by SEA, is a lectin receptor. In association, C-type lectin receptors have been shown to partially mediate the internalization of these antigens, which may highlight the necessity of sugar components in SEA (6, 28,29). This study has deciphered that SEA specifically signals through the C-type lectin receptor Dectin-2, but not Dectin-1 or other receptors such as CD206, CD36, and DAP12.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A feature shared by many helminths is their capacity to suppress TLR-mediated DC activation by microbial PAMP. Numerous studies have reported the inhibitory effects of helminth-derived components on TLR-induced activation as determined by pro-inflammatory cytokine production and expression of MHC class II/costimulatory molecules [28,[33][34][35][36][37][38][39]. The pathways underlying this suppression are, however, still poorly understood.…”
Section: Modulation Of DC Function By Direct Interaction With Helmintmentioning
confidence: 99%
“…43,44 In addition, soluble egg antigens from S. mansoni is enriched in omega-1, which modulates DCs and induces the expression of Foxp3 in T cells in vitro. 45,46 Although the restrained immune response in malaria and schistosomiasis is a problem, the impairment in DC function may become useful for the control of chronic inflammatory conditions. Likewise, DCs exposed to soluble egg antigens and omega-1 acquire modulatory properties and induces Treg cells in CD4 + T cells from non-obese diabetic (NOD) mice, reducing the incidence of spontaneous diabetes.…”
Section: Discussionmentioning
confidence: 99%